Kultura rojevanja na Goriškem v 20. stoletju - Kocijančič, Neli (Obzornik zdravstvene nege, 2020)
Introduction: Pregnancy and birth are very important and emotional events for a woman and her family that result in many changes. The purpose of the qualitative research was to examine the birth culture in the Goriška region in the 20th century through birth stories. Methods: The study used a descriptive interpretative method. We used a dedicated sample of six women who were willing to talk about their birth experience. The youngest of the participants was 66 years old and the oldest was 95 years old. The data were collected through a partially structured interview and analysed using the content analysis method. Results: Four themes were identified: (1) memories of the woman's birth experience, (2) description of the birth experience in terms of the reality of that time, (3) the supportive role of the narrow and wide community in post-natal care and (4) determining a health status through social status. Midwives and close relatives participated in the birth at home, while the maternity event at the hospital was designed by healthcare professionals. The relief of labour pain was not at the forefront. The birth took place in the back position. Birth information was transmitted from one woman to another. The first birth experience is a turning point in experiencing childbirth. Discussion and conclusion: Childbirth and postpartum events have mostly met women's expectations at that particular time and space despite the influence of certain social factors and lack of material goods that are now recognized as essential.
Keywords: interpersonal relationship; izkušnje; mental disorder; obporodna skrb; porodne prakse; psychiatry; rojstvo; treatment measures; zadovoljstvo žensk; zgodovina